Pili and Chpc the Two Adaptor Proteins in Pseudomonas Aeruginosa Chp Chemosensory System - (:unkn) unknown (My University, 2022)
Pseudomonas aeruginosa’s Chp system is an important signal transduction system for its virulence and controls many cellular processes through adenosine 3’,5’ cyclic monophosphate (cAMP) and its interactions with virulence factor regulator (Vfr). Twitching motility, the other output of the Chp system also plays a large role in virulence. This study was completed to better understand the roles the adaptor proteins, PilI and ChpC, fill in the Chp system. The function of the adaptor proteins was investigated through deletion strains via fluorescence microscopy, β-galactosidase assays, twitching motility assays, and surface piliation assays. By viewing these outputs PilI’s status as the dominant adaptor protein of the system was reinforced. ChpC’s role as a structural support adaptor was also reinforced.